Niet Ontvankelijke Verklaard (NO) Decision on the Criminal Case of Land Grabbing Perspective of Justice - Dhinda Ratri Putristira (Fakultas Hukum Universitas Lampung, 2023)
In cases of land grabbing, the overlap between civil and criminal law has created pre-judicial problems. This has resulted in the discourse of justice among those who anticipate law enforcement through criminal proceedings to be insecure. In addition, the Criminal Procedure Code does not recognize decision NO. This article examines the decision of Niet Ontvankelijke Verklaard (NO) in the final decision at the first level of the crime of land grabbing through the perspective of the value of justice. This article uses normative research using case-based, statutory, and conceptual methodologies. Data collection was carried out using literature review tools and interviews. Furthermore, qualitative data analysis was carried out. The findings of the study show that NO's decision in the final decision for the crime of land grabbing at the first level is intended to eliminate inconsistencies between criminal and civil judgments. Still, the Criminal Procedure Code does not recognize NO. Therefore, the NO decision cannot be given in a criminal case. If the indictment cannot be used to prosecute the defendant's actions, the decision can be an acquittal or a decision free from all lawsuits. Regarding the need for a civil decision regarding land ownership, it should be resolved in an interlocutory judgment. NO's verdict in the land grabbing case Number: 376.PID.B/2021/PN KOT does not fulfill the value of justice. Victims cannot get back the items they claim as their own, the public prosecutor cannot prove the accused's guilt, and the perpetrators do not know the exact status of the land. In addition, as a result of NO's decision, the case could not be retried (ne bis in idem), so justice and legal certainty were not achieved.